Produção e aplicação de bioemulsificante isolado de Bacillus subtilis UCP 0146 por fermentação submersa em manipueira - Maia, Patricia Cristina de Veras Souza (2017)
Biosurfactants are tensioactive compounds produced by bacteria, yeasts and filamentous fungi, which have come in the molecule a hydrophobic and other hydrophilic portion, with potential to reduce water surface tension and liquid emulsion with two phases, called Bioemulsifiers. The bioemulsifiers presented potential of application in several industrial areas such as: food, agricultural, pharmaceutical and petrochemical, their characteristics of biodegradability, non-toxic and possibility of production from renewable substrates. In this sense, studies carried out with Bacillus subtilis UCP 0146, investigating a bioemulsifier production, using as substrate the agroindustrial effluent (manipueira). Cultivation was carried out in Erlenmeyer flasks containing 75 mL (100%) of the production medium (manimetry) according to the 23 factorial scale, with 5% inoculum at a concentration of 108 cells / mL, incubated at 30ºC under agitation of 150 rpm for 72h, being evaluated the bioemulsifier produced in the cell free metabolic liquid, the emulsification inde (IE24). As the good, the size of the emulsion droplets, stability to pH, NaCl and temperature. The results showed that the emulsifier had a 95.2% emulsification index with the engine burned oil in the best planning condition, showing a stable emulsion formation at all temperatures and a better response at the temperature of 70ºC (96.0%). Regarding pH was observed in assay 2, an (IE24) of 91.6% relative to salinity or assay 4 represented 92.0%. In addition, no dispersion test showed displacement of 85.3 cm of the oil and the discoloration of methylene blue in aqueous solution, obtained the result of 62.2% removal. The Bacillus subtilis demonstrated the ability to produce bioemulsifiers using a metabolic conversion of the agroindustrial residue, making the bioprocessing economical and great potential in the biotechnological application.